Microeconomics : Textbook - Chyrak, Iryna (Microeconomics : Textbook. – Ternopil : TNEU, 2018. – 223 p., 2018)
The textbook provides an integrated statement of the theoretical and methodological foundations of microeconomics as a science about the basic laws of the market economy functioning at the level of producer and consumer, which reveals the mechanism of decision-making by business entities who seek to achieve maximum needs satisfaction due to limited resources. By its structure and content, the textbook will help students to form the knowledge about the mechanisms and principles of the functioning of economic agents in market conditions, their incentive motives and economic decisions, the ability to analyze the functional relationships between the main economic parameters of the theoretical models and determine the expected results of the decisions, accepted by economic agents in different market situations, use the microeconomic analysis toolkit to evaluate the choice rationality of microsystem decisions, optimize their behavior and apply microeconomic research techniques in order to explain phenomena and analysis of economic results of the business systems. The main textbook’s task is to provide students with the knowledge of the fundamental theoretical and methodological principles of microeconomics and explain the internal relations and relations between economic phenomena, the implantation of skills to use and apply acquired knowledge in solving practical problems, the ability to perform technical and economic calculations related to justification of the optimality of the microeconomic systems decisions, use the microeconomic analysis tools in their further professional activity. Each chapter is devoted to the research of specific phenomena and processes occurring in the microsystem and ends with training which includes basic terms and concepts, questions and tasks for students’ self-control, tasks and tests. The textbook is recommended for students, postgraduates and lecturers of higher education institutions, as well as for anyone interested in microeconomics.